Kunjungan dan Pengenalan Angka Dalam Bahasa Mandarin Pada Usia Dini di Yayasan Panti Asuhan - Holong Marisi Simalango (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Language is a distinctive sign of certain people in communicating, where language can differ from one country to another and from one ethnicity/tribe to another. Mandarin is one of the official international languages that need to be understood and understood today. Various formal and non-formal educations hold Mandarin lessons. Much ethnic Chinese use Mandarin in communicating with fellow ethnic and Chinese descendants in Batam City. Mandarin, especially the city of Batam, is very close to Singapore, whose national language is Mandarin. This condition also affects the residents of Batam to be motivated to understand what is being discussed and to be interested in mastering the Mandarin language. A visit to the Yayasan Panti Asuhan Anak Cemerlang in Batam City provided moral and material support in the form of material on number recognition in Mandarin at an early age for orphanage children